HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KEINGINAN UNTUK SEMBUH PADA PENYALAHGUNA NAPZA DI LEMBAGA PEMASYARAKATAN WIROGUNAN KOTA YOGYAKARTA - Isnaini, Yulia; Hariyono, Widodo; Utami, Isti ken (Universitas Ahmad Dahlan, 2011)
Background: Drugs abuse case like the iceberg phenomenon to appear above the sea surface, while underneath the biggest does not appear. Mortality or the number of the case continue to increase in geometrical progression and risk of disease spread hepatitis B / C of 80% and HIV / AIDS as much as 40-50% and the number was about the abuse of all sections of the community. So that the efforts that seriously not only in prevention but the recovery of those who have become a votary affected which includes the restoration of the medical and social. Family support is considered able to weaken the impact of stress and can directly strengthen the individuals mental health. Goal of this research is to find out the relationship between family support with the desire to recover the drugs abuse Wirogunan correctional facility in Yogyakarta. Method: This was analytical observations cross sectional design. The respondent was 50 people related to criminal cases drugs abuse. Samples taken with the technique Totality Sampling with the criteria set inklusi and eksklusi. Analysis of the data used was the Chi Square test statistics. Results: There was relationship between the support the family with the desire to recover in drugs abuse in the correctional facility Wirogunan Yogyakarta to see the value of Asymp. Sig < á (0.002 <0.05) and the calculated Chi Square 12.605> Chi Square table (df = 2 ? 5.991). Hypothetical possibility or the probability is zero (Ho) is small, so Ho rejected the hypothetical alternative (Ha) accepted. Conclusion: There was relationship between the support family with the desire to recover in drugs abuse in the correctional facility Wirogunan Yogyakarta with the support of the family contributed to 44.9 percent against the desire to recover. Keywords: Family support, desire to recover, drugs abuse.